DISTRIBUTIONAL PATTERNS OF BENTHIC MACROINVERTEBRATE FAUNA IN RIVER BHILANGANA, GARHWAL HIMALAYA, INDIA (Applied Biological Research, 2023)
A study was designed to evaluate the spatial distribution of benthic  macro-invertebrate communities in river Bhilangana, Uttarakhand  (India). The samples were collected during March 2018 to February  2019 at five stations (S1 to S5) from headwater to mouth. The total  mean density of benthic macro-invertebrate community varied  significantly among the stations. Taxonomic composition revealed  that Diptera as the most abundant taxa at S1 (3.6%), S2 (44.1%) and  S5 (36.2%), and Trichoptera at S3 (30.5%) and S4 (34%). However,  at family level, Simulidae was most abundant at S1 (11.2%) and S3  (11.2%), and Chironomidae at S2 (21.2%) and S5 (12.8%). Similarly,  Limnephilidae (21.8%) was the most abundant taxa at S4. The assemblage patterns varied longitudinally from S1 (Simulidae - Limnephilidae - Philopotamidae - Chironomidae) to S2  (Chironomidae - Simulidae), S3 (Simulidae - Philopotamidae), S4  (Limnephilidae - Simulidae) and S5 (Chironomidae - Simulidae).  Ordination technique PCA identified characteristic taxa at S1  (Belostomatidae and Vellidae), S2 (Chironomidae, Tabanidae and  Psephenidae), S3 (Glossosomatidae, Hydropsychidae, Psychomyiidae,  Agrionidae, Blepharoceridae and Leptidae), S4 (Caenidae,  Haliplidae, Dryopidae and Dixidae) and S5 (Tipulidae and  Corydalidae). The variation in the characteristic taxa at these  stations was primarily attributed to substrate heterogeneity and  forest type patterns; conifer-oak rhododendron, oak-rhododendron,  pine-oak, etc.
Keywords: Bhilangana river; Chironomidae; forest type; PCA; Simulidae; spatial distribution; taxonomic composition